Análise das políticas públicas da educação inclusiva: um olhar sobre as adaptações curriculares para alunos com deficiência intelectual na escola pública no município de Macapá-AP - Silva, Maria Rita Paula da (2015)
This research is directed toward analyzing the public policies of inclusive education, specifically, those related to curricular adaptations for students with intellectual deficiencies who are in the public school system of the Municipality of Macapá, in Amapá. To do this bibliographic and documental research was carried out. Bibliographic and documental research was done in books, online publications, official documents of national range and documents which orient special education of the municipality of Macapá. Also researched were current educational legislations which present the proposal of inclusive education. Didactically the results of the research were organized in chapters thus distributed: (1) Inclusive education for the intellectually deficient student: historical trajectory and definitions. In this chapter the historical journey of inclusion was dealt with. We sought to define inclusive education and also deal with intellectual deficiency and inclusion. (2) Inclusive Educational Policies, which deals with the international movements with regard to the proposal of inclusive education as well as with the legislation of inclusion in Brazil and in the municipality of Macapá. The focus was on the organizational structure of specialized educational services in the municipality of Macapá; as well as on the modalities and forms of service and the guiding principles and the legal base of specialized educational services. (3) Curricular adaptation focusing on inclusion, which deals with the curriculum, its conceptualizations and definitions. In sequence, we discuss the why of the need for curricular adaptations. Reference was also made to curricular adaptation focusing on inclusion, referring to the large and small adaptations. We discuss the school curriculum and the student with intellectual deficiencies, seeking to raise important issues about the changes that are necessary in order to better serve the student with intellectual deficiencies.